(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Fatigue failure is an important phenomenon that occurred in the mechanical and structural systems. Furthermore, the failure due to fatigue load causes losing in that system. So many researches studying the fatigue behavior and improving the design of mechanical and structural systems in order to increase the fatigue resistance of these systems. In this work, the effects of notch position and load magnitude on fatigue behavior were studied. In order to study the fatigue life of the test specimens due to make V- notched, the rotating cantilever beam samples were used. Also, the temperature distribution along testing specimens was monitoring of IR camera during the fatigue tests. Numerical model has been done by using ANSYS Workbench 15.0. The comparison between experimental and numerical results was made, also the hardness of the fractured surfaces was measured. The results show that, the fatigue life of the test specimens can be increased by making a notch in the appropriate position. Also, there is a similarity between experimental and numerical results. IR camera gave a good expectance to the fracture position from changing in temperature distribution along the test specimens. Finally, the area of sudden fracture of the fractured surfaces reduced directly with load magnitude and inversely with notch shifting away from edge region.